Studies in the Neotropical Apocynaceae LII: A synopsis of Laxoplumeria with three new species - Morales, J. Francisco; Morais, Isa Lucia De (Phytotaxa, 2018)
This synopsis provides a key, genus description, synonymy, species descriptions, distribution, habitat, vernacular names (when available), specimens examined, illustrations and distribution map for the five species of Laxoplumeria known. A new synonym (L. macrophylla) is proposed and three new species (L. aberrans, L. longipetiolata, L. verticillata) are described.